The Strategy Of SD Pusri In Improving Educational Quality - Irmayani, Herni; Wardiah, Dessy; Kristiawan, Muhammad (Jurnal Dosen Universitas PGRI Palembang)
AbstractIn this qualitative research, the focus was the strategy SD Pusri in Improving the quality of teachers and education personnel, quality of facilities and infrastructure and quality of management. The results obtained in this study indicate that SD Pusri strategy in improving the quality of educators and educational personnel through routine supervision of principals, delegation of authority, training, upgrading, seminars, technical guidance, workshops, and training, and to evaluate the performance of educators and educational staff offset by rewards. The strategy on improving the quality of facilities and infrastructure was done by coordinating through the early budgetary meetings, gradual fulfillment of facilities, comparative study and fulfillment the computer facilities. For management strategies, SD Pusri performed planning, program implementation and evaluation activities. The findings obtained by the Principal tend to use the concept of Total Quality Management (TQM) in the management process. Starting from the process of admission until the new graduation involving all parties. In addition, schools are always oriented to the satisfaction of school residents both internally and externally and the school together continuously in the form of improving the quality of education through various activities involving the school community. Besides being supported by parents and the community, the school also has good facilities from Yayasan Sosial Pendidikan (YSP) Pusri.Index Terms: Strategy, Quality of Education, SD Pusri